Strength Properties of Rice Husk Ash Concrete Under Sodium Sulphate Attack - Putra Jaya, Ramadhansyah; Che Wan, Che Norazman; Hainin, Mohd Rosli; Mohd Warid, Muhammad Naqiuddin; Wan Ibrahim, Mohd Haziman; Mohamed Nazri, Fadzli; Arshad, Mohd Fadzil (International Journal of Integrated Engineering, 2018)
The use of pozzolanic materials in concrete provides several advantages, such as improved strength and durability. This study was investigated the strength properties of rice husk ash concrete under severe durability (sodium sulphate attack). Four RHA replacement levels were considered in the study: 10%, 20%, 30%, and 40% by weight of cement. The durability performance of the RHA blended cement exposed to sodium sulphate solution was evaluated through compressive strength, reduction in strength, and weight loss. Test results showed that RHA can be satisfactorily used as a cement replacement material in order to increases the durability of concrete. Concrete containing 10% and 20% RHA replacements showed excellent durability to sulphate attack. The results also indicate that the amount of Ca(OH)2 in the RHA blended cement concrete was lower than that of Portland cement due to the pozzolanic reaction of RHA.